FIELD WORK IN FOUR DIFFERENT COMMUNITIES AFFECTED BY FLOOD IN THE YEAR 2022 BETWEEN THE MONTH OF JULY TO SEPTEMBER WITH MMC AND JERE LOCAL GOVERNMENT OF BORNO STATE: TRIP REPORT - Abraham Abiodun Bamisile (World Journal of Biology Pharmacy and Health Sciences, 2026)
This trip report presents the findings of a field assessment conducted between July and September 2022 in four flood-affected urban communities (Kogin Tipa, Maduganari, Wulari-Jerusalem, and Sabongari-Gwange) within the Maiduguri Metropolitan Council (MMC) and Jere Local Government Areas of Borno State, Nigeria. The assessment aimed to evaluate the impact of recurrent flooding, identify underlying causes, and propose mitigation strategies. Through on-site observations and interviews with community residents, the study identified severe infrastructure damage, property loss, health risks, and disrupted transportation. Key drivers of the flooding included rapid urbanization, poor land-use planning, indiscriminate waste disposal in river channels, and climate change effects. Despite government warnings, many residents refuse to relocate due to ancestral ties and livelihood concerns. The report recommends implementing robust flood prevention infrastructure, enforcing land-use planning, developing early warning systems, and promoting green infrastructure to mitigate future flood impacts and ensure environmental sustainability.